The roles of NGOs for the livelihood of Rohingya refugees - Mohd Arshad, Mohd Ramlan; Ajis, Mohd Na’eim; Abdullah, Azreen (UiTM Cawangan Johor, 2022)
This research is concerned about the Rohingya experiences during their migration from Myanmar to Malaysia and the strategies they embarked to integrate with the local people through NGOs. Qualitative research with in-depth interviews were employed on 3 NGOs set up by Rohingyas refugees from Klang Valley, Malaysia. The responds from informants were analyzed using NVIVO software for transcription and analysis. Thematic analysis was used to blend the information from informants based on the nodes created namely as registration with UNHCR, access to education and medical aid. Rohingya's NGOs played significant roles to help their own communities in Malaysia. Rohingya refugees were satisfied that the NGOs had helped them much but they still faced discrimination due to the law of Malaysian government which does not recognized the status of refugees. They faced issues of limited access to health, formal education and safety protection. Rohingya NGOs played significant strategies to ensure their communities get such basic needs to pursue their life. However, legality issues of refugees remained as the main barrier for livelihood of Rohingya in Malaysia. Currently, there is no refugee policy in Malaysia, thus policymakers should established and align with the international standard of practice in managing Rohingya refugees. The involvement of NGOs should be considered to eliminate negative view of citizens on the migration and integration of Rohingya refugees in Malaysia. Collaboration efforts among government agencies, UNHCR and NGOs may help in resolving untangling issue of refugees in Malaysia for the past three decades.